Sexual Violence in Indonesia and Malaysia: A Comparative Study - Kuswardani, Kuswardani (Jurnal Media Hukum, 2019)
Sexual violence (rape) especially committed by boyfriend has been growing rapidly these days. However, the Penal Code cannot be dealt with this issue. In such a case, the sexual intercourse is usually conducted without violence or under threat of violence, but rather based on consent (love). Penal reform should address this issue to accord with the current global development. This paper describes the comparison between the Indonesian Penal Code and the Malaysian Penal Code in regulating rape. The result shows that the formulation of rape in Malaysian Penal Code is broader than its Indonesian counterpart. Under the Malaysian Penal Code, rape is punishable whether it is conducted with or without consent. It seems that the penal reform in Indonesia should adopt the Malaysian approach in order to provide better protection for women from sexual violence. This is also in line with the Beijing Declaration 1993 and the development of the issues in other countries.Â